Implementasi Nilai-Nilai Profil Pelajar Pancasila di SMAN 2 Medan - Nurmila Hidayana; Liesna Andriany (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the form of implementation of the Pancasila student profile at SMAN 2 Medan.The method used is descriptive with a qualitative approach. The research results show that the Pancasila student profile values ​​have been implemented intensively, namely 1) The profile of faith, devotion to God Almighty and noble morals is realized through JUBAH (Juma'at Worship) activities which are carried out every Friday morning and carrying out congregational prayers. 2) The global diversity profile is implemented through discussion and study of various foreign cultures. 3) The mutual cooperation profile is realized through community service activities, group discussions, and the preparation of OSIS work programs. 4) An independent profile is realized through completing daily tasks, taking exams, as well as returning and fixing books in the library. 5) The creative profile is realized by encouraging students to create new things, carrying out activities to recycle waste into useful items in the P5 program. 6) Critical reasoning is carried out through activities to get students used to asking questions in class, discussing, giving arguments to the problems raised, criticizing and respecting differences of opinion. The results of this research can be used as a model in implementing the Pancasila student profile in high school.